Karakteristik Protein Dan Asam Amino Daging Sapi Bali Dan Wagyu Pada Penyimpanan Suhu Dingin 4°C (CHARACTERISTIC OF PROTEIN AND AMINO ACIDS OF BALI AND WAGYU BEEF AT COLD STORAGE TEMPERATURE 4°C) - Sinlae, Reny Navtalia; Suwiti, Ni Ketut; Suardana, I Wayan (Buletin Veteriner Udayana, 2015)
Research has been conducted to determine the effect of breed (bali cattle and wagyu) andperiod time at cold storage temperatures (4°C) of beef protein and amino acids charateristics. Thisstudy used the completely randomized factorial design. First factors were type of beef (bali cattle and wagyu) and the second factors were period storage at cold temperature 4°C (day of 0, 3, 7, and14). The bands of proteins were analyzed using SDS-PAGE method while the amino acids wereanalized using HPLC method. Data were analyzed by analyse of variance. The result showed thatthe storage time affected to the profil of protein bands of bali and wagyu beef after 7 days and 14days of storage, while the concentration of amino acids has been decreased. This means that theactivity of proteolytic enzymes in meat stored at 7 days was degrading proteins and affected thequality of meat. The conclusion indicated that bali and wagyu beef showed differencescharacteristic of protein (the thickness and number of bands) as well as significant differences ofthe amino acid Phenylalanine in wagyu beef compared with bali beef. The period time at coldstorage temperature 4°C showed real effect to the decline of the amino acid histidine, phenylalanineand isoleucine of bali and wagyu beef.
Keywords: protein band; amino acids; bali and wagyu beef